Buntning av grot med lastbilsmonterad utrustning - Edman, Torbjörn (2009)
During the transportation of logging residues (LR) the material´s low density is a problem that results in low use of pay-load capacity. Comminution or compression of LR are possible methods to increase pay-loads. In the present thesis studied a bundling machine which was mounted on a truck chassis, and the subsequent transport and crushing. The truck bundler created bundles that were larger and longer than other bundling equipment on the market. The objectives were to determine the total time consumption and its allocation over work element and machinery, to measure dry matter (DM) content of green and brown LR-bundles. In addition the objectives was also, the system's economy was addressed.